Genetic differences in aluminium accumulation in the grains of field grown Aegilops and Triticum - Ivana Maksimović; Rudolf Kastori; Marina Putnik-Delić; Vojislava Momčilović; Srbislav Denčić; Milan Mirosavljević (Plant, Soil and Environment, 2020)
Plant species and genotypes differ considerably with respect to the accumulation of mineral elements. This study examined the accumulation of aluminium (Al) in Aegilops and Triticum species with different genomes (AA, BB, BBAA, BBAADD and DD) and correlations between concentration of Al in the grain and features of the spike. Twenty different genotypes were included in three-year field experiments. The examined species and genomes differed significantly in their Al concentration in grain. The highest concentrations of Al were found in the grains of wild diploid Aegilops speltoides (BB genome), and the lowest in tetraploids (BBAA genome). A significant positive correlation was found between the concentration of Al in the grain and spike length, while negative correlations were found between concentration of Al in the grain and the number of grains per spike, grain weight per spike and thousand grains weight. The presence of higher Al content in the individual grains of tetraploid and hexaploid wheat with respect to diploid ancestors suggests that during the increase in ploidity the capacity of plants to uptake Al from soil increased concomitantly with the increase of grain capacity to serve as Al sink.